Budgeting and Saving Effectiveness as the Main Pillar of Sustainable Personal Financial Management - Prakoso, Teguh; Apriliani, Rina (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Personal financial management is an important aspect of achieving financial stability and success. This research examines the importance of effective budgeting and saving practices as key components of personal financial management. The research shows that budgeting is important in personal financial management as it provides a clear framework for managing income and expenditure. By having a detailed budget, individuals can monitor their cash flow, ensure that they allocate funds to essential needs, and identify areas where spending can be reduced. Budgeting also helps set short-term and long-term goals, encouraging financial discipline and responsibility. Studies indicate that individuals who consistently follow a budget tend to have better financial health and are less trapped in debt. In addition to budgeting, effective saving practices are a key component of personal financial management. Saving is important to deal with financial emergencies and achieve future goals, such as home purchase, education, or retirement. Regularly setting aside a portion of income into savings can help individuals build financial reserves and reduce reliance on loans or credit. Studies have also found that saving regularly can increase financial well-being and reduce money-related stress. Therefore, effective budgeting and saving are two key pillars that complement each other in achieving sustainable personal financial stability.